2021
DOI: 10.1016/s1473-3099(21)00075-x
|View full text |Cite
|
Sign up to set email alerts
|

What does 95% COVID-19 vaccine efficacy really mean?

Abstract: also found in a Lancet Infectious Diseases Editorial. 4 In the examples used in the Editorial, those protected are those who would have become diseased with COVID-19 had they not been vaccinated. This distinction is all the more important as, although we know the risk reduction achieved by these vaccines under trial conditions, we do not know whether and how it could vary if the vaccines were deployed on populations with different exposures, transmission levels, and attack rates.Simple mathematics helps. If w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 2 publications
1
29
0
3
Order By: Relevance
“…The problem does not appear to be confined to popular outlets since, as pointed out by Olliaro (2021) , incorrect interpretation of the significance of VE can also be found in prestigious scientific journals, including an editorial in Lancet Infectious Diseases:…”
Section: Introduction: the (Non-obvious) Concept Of Vaccine Efficacymentioning
confidence: 99%
“…The problem does not appear to be confined to popular outlets since, as pointed out by Olliaro (2021) , incorrect interpretation of the significance of VE can also be found in prestigious scientific journals, including an editorial in Lancet Infectious Diseases:…”
Section: Introduction: the (Non-obvious) Concept Of Vaccine Efficacymentioning
confidence: 99%
“…It is essential to understand the efficacy of the approved vaccines (originated from Asia). The approved vaccines have shown efficacy in clinical trials, and it is essential as it protects both the person and a country's population [53,54]. In general, it was observed that most of the approved COVID-19 vaccines had efficacy in the range of 70-95% (Table 1).…”
Section: The Effectiveness Of the Approved Vaccines Originated From Asiamentioning
confidence: 99%
“…Since the first day, the Italian ministry of health, through the special pandemic commissioner, publishes daily the vaccination data on a GitHub data repository (Italian Special Pandemic Commissioner, 2021) that provides an in-depth vision of both the delivered and administered doses. in preventing the hospitalization of an infected person (Anand and Stahel, 2021;Benenson et al, 2021;Olliaro, 2021;Vasileiou et al, 2021). Since the second wave of Covid-19, which started in Italy at the beginning of October 2020 (as of May 2021, Italy is experiencing the deflation trend of the third wave, which started towards the end of February 2021), Covid-19 patients die only in hospitals (Ciminelli and Garcia-Mandicó, 2020).…”
Section: An Alternative Approach To Vaccinationmentioning
confidence: 99%
“…Specifically, the 32 tt  interval is 7, 14, and 14 days for Pfizer/BioNTech, Moderna, and Vaxzevria vaccines respectively (Mansourabadi et al, 2020;Olliaro, 2021).…”
Section: Immunization Profilementioning
confidence: 99%